Konstruksi Makna, Identitas Lokal, dan Spiritualitas dalam Folklor Batu Kuda: Kajian Semiotika Peirce - Firmansyah, Arif; Vatahhayati, Nova Aldhita; Malik, Miftahul (Badan Pengembangan dan Pembinaan Bahasa, 2025)
This study aims to obtain and describe the moral value of the oral tradition of Horse Stone folklore based on Pierce's semiotics in classifying objects based on the classification of symbols, icons, and indices. Pierce's use of semiotics is related to the uses possessed by folklore itself. All types of folklore, whether oral folklore, partly oral folklore or non-oral folklore, have uses or functions that are very important for human life. This makes folklore in life can describe the way a person involves himself in the midst of community life. The method used qualitative method with a semiotic approach, because the results of data that have been generated and collected on the Horse Stone folklore will be described in the form of written data. Finally, the results of data processing are used as a proposal for literature teaching materials in high school based on the Independent Curriculum in the form of modules. Learning folklore or folklore has a very important role in efforts to preserve noble values and local cultural wisdom. In education, folklore can be used as a learning medium and can be used as learning material for students. The use of folklore as an educational medium can be utilized in various disciplines, which of course the selection of folklore used must be right with the subject matter to be delivered. The use of folklore as an educational medium also acts as one step in preserving existing local culture. Therefore, getting used to delivering lessons through teaching materials is an effort to preserve folklore as part of culture, both protection, utilization and development of folklore in the future. Abstrak Penelitian ini bertujuan untuk memperoleh dan mendeskripsikan nilai moral dari tradisi lisan folklor Batu Kuda ini berdasarkan semiotik Pierce dalam penggolongan objek berdasarkan klasifikasi simbol, ikon, dan indeks. Penggunaan semiotika Pierce ini berkaitan dengan kegunaan yang dimiliki oleh folklor itu sendiri. Keseluruhan jenis folklor baik folklor lisan, folklor sebagian lisan ataupun folklor non lisan, memiliki kegunaan atau fungsi yang sangat penting bagi kehidupan manusia. Hal tersebut membuat folklor dalam kehidupan itu dapat menggambarkan cara seseorang melibatkan dirinya di tengah-tengah kehidupan masyarakat. Metode yang digunakan metode kualitatif dengan pendekatan semiotik, karena hasil data yang telah dihasilkan dan dikumpulkan pada folklor Batu Kuda akan dideskripsikan dalam bentuk data tertulis. Terakhir hasil pengolahan data dijadikan sebagai usulan bahan ajar sastra di SMA berdasarkan Kurikulum Merdeka berbentuk modul. Pada isi cerita folklor Batu Kuda ini, peneliti mendapatkan 11 hasil analisis data yang menggunakan semiotika Pierce yang pengklasifikasianya berdasarkan objeknya yang di dalamnya terdapat : Ikon adalah tanda yang menyerupai bentuk objek aslinya. Terdapat tiga (3) data dari hasil analisis ikon pada folklor Batu Kuda. Indeks adalah tanda yang berkaitan dengan hal yang bersifat kausal, atau sebab akibat. Terdapat tiga (3) data dari hasil analisis indeks pada folklor Batu Kuda. Dan Simbol adalah tanda yang berkaitan dengan penandanya dan juga petandanya. Terdapat lima (5) data dari hasil analisis simbol pada folklor Batu Kuda. Dengan total keseluruhan data yang diperoleh dalam analisis semiotika pada folklor Batu Kuda yaitu berjumlah sebelas (11) data yang terdiri dari tiga pengkategorisasian.